Peningkatan Hasil Belajar IPA Materi Menggolongkan Hewan Berdasarkan Jenis Makanannya Melalui Penerapan Metode Picture and Picture - Taufiqur Rohman; Laily Syafa'ah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
ABSTRAC The learning process of Natural Sciences (IPA) in MI Tarbiyatul Ulum Jembrak Pabelan District. Semarang, still uses the expository method where the teacher explains the material and students only listen and take notes. So the method used by the teacher in the learning process does not improve the learning outcomes of science. It requires student participation in other activities such as asking questions, doing exercises, doing homework (homework), going to the front of the class, holding discussions, and issuing ideas or ideas.By applying the picture and picture method the type of research the researcher uses is Classroom Action Research, which includes 4 stages: planning, action, observation, reflection. The results of the implementation are evaluated in reflection to compile improvements up to two cycles, while observation, documentation, and formative tests are used research data collection techniques.Based on classroom action research that has been done, it can be obtained that the learning outcomes of students from the first cycle reached KKM by 16 students or 74.09% with the second cycle reaching KKM by 20 students or 90.9%. So there is an increase in learning outcomes of 4 students or 18.18%. It can be concluded that the method of picture and picture can attract the attention of students so that it can improve the learning outcomes of science, this is shown by students actively involved in the learning process in class and satisfying test results. Keywords : Picture and Picture, Learning Outcomes, Classifying Animals